Comics as Literary Compasses and Kaleidoscopes - David E. Low; Francisco L. Torres (University of Oklahoma Libraries, 2022)
Through an analysis of published graphic novels and comics created by schoolchildren, and building upon Rudine Sims Bishop's literary metaphors, we discuss how comics serve as compasses and kaleidoscopes that allow readers/composers/educators to center justice in the storying process. We argue that the comics medium provides readers and authors specific affordances (interiority, multiperspectivity, fragmentation, ambiguity, juxtaposition, and focalization) for bending reality and framing stories of the unseen, unheard, and hidden in the margins. We address teachers directly in exploring what's possible when texts are read kaleidoscopically to engage the multiperspectival/multiversal/liminal nature of a robustly multimodal medium.